ChemInform Abstract: Cu/Pd‐Catalyzed C‐2—H Arylation of Quinazolin‐4(3H)‐ones with (Hetero)aryl Halides. Issue 16 (March 2016) - Godeau, Julien; Harari, Marine; Laclef, Sylvain; Deau, Emmanuel; Fruit, Corinne; Besson, Thierry
Abstract: The regiospecific arylation of N‐3‐substituted quinazolinones with a wide range of aryl or (hetero)aryl halides under microwave irradiation is studied.